Relationship between Attitudes to Child Nursing College Students Perceived Punishment, Child Abuse Awareness and Knowledge. (Medico Legal Update, 2020)
Background/Objectives: This study was conducted to present the basic data for developing education programs for nursing students through correlation research between the awareness and knowledge of child abuse and the attitude toward child corporal punishment for nursing students, and to contribute to the development of customized education programs by grade.Methods/Statistical analysis: The subjects of this study were 200 nursing students in first and second grade of a university located in D city. Data collection was conducted from Oct 1 to Oct 30, 2018.With the collected data, using SPSS Program.Findings: As a result, the awareness of child abuse had a statistically significant difference in grade, completion of child abuse prevention education, and completion of education related to child abuse after entrance.Improvements/Applications: In conclusion, in order to increase the awareness and knowledge of child abuse of nursing students and to cultivate their attitude toward child corporal punishment which is unallowable, it is thought that the indirect experience through the curriculum and non-curriculum of child nursing science of department of nursing will be helpful.